A visiting otolaryngology team in northern Ontario - demographics, clinical presentation and barriers to access - Emma Campisi; Christopher Hong; Eric Monteiro; Vincent Lin; Barbara Russell; Paolo Campisi (James Cook University, 2024)
Context: Approximately 20% of Canadians reside in rural or remote communities where access to medical specialties such as otolaryngology remains challenging due to long wait times and distance to services. The purpose of this study was to characterize patient demographics, common clinical diagnoses, and barriers to accessing otolaryngology services, in a remote Northern Ontario setting. A secondary objective was to describe a care model that provides multi-subspecialty otolaryngology services to a remote community. Issue: A team of academic otolaryngologists provided annual (2020-2021) subspecialty services in otology, neurotology, rhinology, head and neck oncology, and pediatrics to a remote hospital with admitting, general anesthesia and surgical resources. Data regarding patient demographics, otolaryngology-related diagnosis, wait times and distance travelled were recorded. Data were obtained for 276 patients treated in the clinic. The median age was 47 years (range 0-85 years). The most common otolaryngological conditions were hearing loss (n=62) and nasal obstruction (n=34). Nearly 30% of patients traveled further than 150 km to access care, and 62% waited 3-6 months for a consultation. Lessons learned: This is the first study to characterize the demographics and range of otolaryngological disorders encountered in a remote Northern Ontario setting. The results have identified specific otolaryngology needs and barriers to access to care. The data can be used to guide healthcare providers and administrators on resource allocation to optimize the delivery of otolaryngology services.